COMMUNICATIONS: 5. URINARY TRACT TUBERCULOSIS: CASE SERIES - Taher, M.A. (The ASEAN Journal of Radiology, 2023)
Urinary tract tuberculosis is a rare disease and therefore, we like to report the following cases.